2013
DOI: 10.6000/1929-5634.2012.01.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Three Different Galenic Liquid Formulations Compounded from Tablet Containing Glibenclamide

Abstract: The suspensions of sulfonylurea glyburide (glibenclamide) are compounded extemporaneously for patients suffering from transitional and Permanent Neonatal Diabetes mellitus (PND). The purpose of this study is to compare the stability of three different galenic liquid formulations compounded from tablet containing glibenclamide. The samples were stored at refrigerated (2-8°C) and room temperature and analyzed at different times. All formulations analysed are stable for at least 90 days, but only two guarantee th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Only one study has reported details of glibenclamide oral liquid formulations prepared only from tablets and described their chemical stability over 90 days 14. Our study adds more information, with raw material based formulations and microbiological studies, together with other important characteristics, such as colour, odour, resuspendibility, pH, chemical stability and morphology of suspended particles.…”
Section: Discussionmentioning
confidence: 90%
“…Only one study has reported details of glibenclamide oral liquid formulations prepared only from tablets and described their chemical stability over 90 days 14. Our study adds more information, with raw material based formulations and microbiological studies, together with other important characteristics, such as colour, odour, resuspendibility, pH, chemical stability and morphology of suspended particles.…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, the patient developed severe hypo-DOI: 10.1159/000525989 glycaemia after the first dose. Possible causes could be the use of an extemporaneous solution of this medication with suspected rapid settling, suboptimal tablet dispersion, and inconsistent dose uniformity [22], resulted in dosing inaccuracy. However, there are reports of the effective use of such formulations in neonates with KCNJ11 mutations [23,24].…”
Section: Early Postnatal Glibenclamide Treatmentmentioning
confidence: 99%